Recovery of the Irreversible Crystallinity of Nanocellulose by Crystallite Fusion: A Strategy for Achieving Efficient Energy Transfers in Sustainable Biopolymer Skeletons. Issue 46 (7th October 2021) - Daicho, Kazuho; Kobayashi, Kayoko; Fujisawa, Shuji; Saito, Tsuguyuki
Abstract: Crystallites form a grain boundary or the inter‐crystallite interface. A grain boundary is a structural defect that hinders the efficient directional transfer of mechanical stress or thermal phonons in crystal aggregates. We observed that grain boundaries within an aggregate of crystalline cellulose nanofibers (CNFs) were crystallized by enhancing their inter‐crystallite interactions; multiple crystallites were coupled into single fusion crystals, without passing through a melting or dissolving state. Accordingly, the lowered crystallinity of CNFs, which has been considered irreversible, was recovered, and the thermal energy transfer in the aggregate was significantly improved. Other nanofibrous crystallites of chitin also showed a similar fusion phenomenon by enhancing the inter‐crystallite interactions. Such crystallite fusion may naturally occur in biological structures with network skeletons of aggregated fibrillar crystallites having mechanical or thermal functions. Abstract : Grain boundaries within an aggregate of crystalline cellulose nanofibers (CNFs) are crystallized by enhancing their inter‐crystallite interactions; multiple crystallites are coupled into single fusion crystals without passing through a melting or dissolving state. Accordingly, thermal energy transfer within the CNF aggregate is significantly improved.